2020
DOI: 10.2174/1573397115666190916142945
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Systemic Lupus Erythematosus in Tunisian Males

Abstract: Purpose: Systemic Lupus Erythematosus (SLE) in males is rare. Clinical and biological features, as well as, the outcome may differ comparatively to female patients. The purpose of our study is to define these clinical and biological features in Tunisian male patients presenting SLE. Methods: A mono-centric, retrospective and descriptive study of 96 patients followed for SLE out of which 21 are males. A comparative study was then performed between male and female patients groups. Results: Sex-ratio female/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Lupus anticoagulant positivity is more common in men, combined with smoking and alcohol use, which is related to a higher prevalence of thrombosis in male SLE than in female SLE ( 96 98 ). Additionally, renal, hematological, and neurological involvement, as well as serositis features prominently in male SLE, leading to rapid organ damage compared to female SLE ( 94 , 99 ). The increase in autoantibody production and the development of lupus nephritis in male SLE is presumed to be due to the global deletion of ERα or especially in B cells ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lupus anticoagulant positivity is more common in men, combined with smoking and alcohol use, which is related to a higher prevalence of thrombosis in male SLE than in female SLE ( 96 98 ). Additionally, renal, hematological, and neurological involvement, as well as serositis features prominently in male SLE, leading to rapid organ damage compared to female SLE ( 94 , 99 ). The increase in autoantibody production and the development of lupus nephritis in male SLE is presumed to be due to the global deletion of ERα or especially in B cells ( 98 ).…”
Section: Resultsmentioning
confidence: 99%
“…In relation to disease activity, SLEDAI scores and lupus severity of disease index scores did not differ significantly between the sexes in most studies (90,94,95,98,104). Conversely, renal damage is a major concern in male SLE, as several studies reported that male sex is a strong predictor of baseline damage and men have a high risk of developing chronic renal failure (91,92,(105)(106)(107)(108)(109).…”
Section: Clinical Features and Outcomes In Male Systemic Lupus Erythe...mentioning
confidence: 96%
See 2 more Smart Citations
“…All participants met the 1997 American College of Rheumatology (ACR) revised criteria for the classification of SLE (26); SLE patients with cancer, infectious diseases, and other rheumatic diseases, were excluded. For some analyses, the 100 SLE patients were divided into an inactive group (n=50) and an active group (n=50) according to their SLEDAI score [if ≥10, they were considered clinically active (27)]. For other analyses, these participants were grouped into a non-lupus nephritis group (non-LN, n=52) and lupus nephritis group (LN, n=48) according to the results of renal biopsy in department of pathology in our hospital [including1 class II, 9 class III, 25 class IV, 6 class V, 5 class III + V, and 2 class VI, using the International Society of Nephrology/Renal Pathology Society (ISN/RPS) 2003 lupus nephritis classification (28)].…”
Section: Data Collectionmentioning
confidence: 99%